Analysis of Antimicrobial Resistance Genes (ARGs) in Enterobacterales and A. baumannii Clinical Strains Colonizing a Single Italian Patient - Alessandra Piccirilli; Elisa Meroni; Carola Mauri; Mariagrazia Perilli; Sabrina Cherubini; Arianna Pompilio; Francesco Luzzaro; Luigi Principe (MDPI AG, 2023)
The dramatic increase in infections caused by critically multidrug-resistant bacteria is a global health concern. In this study, we characterized the antimicrobial resistance genes (ARGs) of K. pneumoniae, P. mirabilis, E. cloacae and A. baumannii isolated from both surgical wound and rectal swab of a single Italian patient. Bacterial identification was performed by MALDI-TOF MS and the antimicrobial susceptibility was carried out by Vitek 2 system. The characterization of ARGs was performed using next-generation sequencing (NGS) methodology (MiSeq Illumina apparatus). K. pneumoniae, P. mirabilis and E. cloacae were resistant to most β-lactams and β-lactam/β-lactamases inhibitor combinations. A. baumannii strain was susceptible only to colistin. The presence of plasmids (IncN, IncR, IncFIB, ColRNAI and Col (MGD2)) was detected in all Enterobacterales but not in A. baumannii strain. The IncN plasmid and blaNDM-1 gene were found in K. pneumoniae, P. mirabilis and E. cloacae, suggesting a possible transfer of this gene among the three clinical species. Conjugation experiments were performed using K. pneumoniae (1 isolate), P. mirabilis (2 isolates) and E. cloacae (2 isolates) as donors and E. coli J53 as a recipient. The blaNDM-1 gene was identified by PCR analysis in all transconjugants obtained. The presence of four different bacterial species harboring resistance genes to different classes of antibiotics in a single patient substantially reduced the therapeutic options.